The Application of Artificial Intelligence in HR Recruitment Strategies Impacts Startupreneur Buying Interest: Penerapan Kecerdasan Buatan dalam Strategi Rekrutmen SDM Berdampak pada Minat Beli Startupreneur - Santoso, Nuke Puji Lestari; Hardini, Marviola; Farail, Maulana Faqih; Fitriani, Anandha; Vaher, Kristina (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
The development of Artificial Intelligence (AI) in Human Resource Management (HRM) provides an opportunity to increase efficiency and effectiveness in the recruitment process in the modern business era. In this context, AI supports the achievement of the Sustainable Development Goals (SDGs), especially goal 8, namely decent work and economic growth, and goal 10 on reducing inequal ity. AI allows companies to optimize the candidate selection process by using sophisticated algorithms that can analyze large amounts of data to find the most suitable candidates for the organization needs. Thus, AI plays an important role in creating a faster, more accurate, and bias-free recruitment process, which ultimately improves the quality of the workforce. However, the application of AI in recruitment also faces challenges related to technology integration, personal data protection, and potential bias in algorithmic decision-making. This study examines the role of AI in optimizing the recruitment process and its contribution to achieving the SDGs. The study also evaluates the impact of AI on recruitment decisions and company productivity and provides recommendations for more effective implementation in modern business.